Mapping the advisory needs and information ecosystems of potato farmers in Nigeria and Kenya. Sub-lever inclusive design & user research - Simiyu, Maryfaith; Ortiz Crespo, Berta; Muller, Anna (2024)
MercyCorps Agrifin in collaboration with Excellence in Agronomy Initiative, The International Potato Center and The Alliance of Bioversity and CIAT are currently providing advisory content to organizations working directly with farmers – such as CoAmana, Every Farmer and Farm Monitor. However, questions around the specific content of the advisory and the format remained. To answer those questions a Human Centered Design exploratory study was conducted, aiming to understand which advisory can meet the needs, preferences, and challenges that farmers experience.